Cognitive behavioral intervention in sport psychology: A case illustration of the exposure method with an elite athlete. Issue 3 (2nd September 2017) - Gustafsson, Henrik; Lundqvist, Carolina; Tod, David
ABSTRACT: One common method in Cognitive behavior therapy (CBT) to treat anxiety problems is exposure, but there are few articles examining its applicability to sport. The aim of this article is to give a background of the use of exposure in sport and present a case of how exposure can be used with athletes. The athlete was a 17-year-old female cross-country skier with high levels of performance anxiety. In the case description, common procedures in CBT such as behavioral analysis, psychoeducation, and exposure are presented, as well as how anxiety can be managed. After the intervention the athlete perceived lower levels of anxiety as well as improved behavioral repertoire (e.g., less avoidant behaviors and more functional sport-specific behaviors). This case may be used to help practitioners consider the use of exposure in competitive sports.